Human security and external burden-sharing: the European approach to refugee protection between past and present. Issue 2 (17th February 2016) - Biondi, Paolo
Abstract : The discourse surrounding the link between human security and the European Union's policy on external burden-sharing is connected to the concept of securitisation developed in the 1990s, when the language of human security was first used to promote solutions in the regions-of-origin of refugees through external burden-sharing. External forms of burden-sharing, nevertheless, can be traced back to the UNHCR's use of its 'good offices' in the 1960s to promote ′regional solutions in Asia, and reflect a slow evolution since the adoption of the 1951 Convention. In order to understand this evolution this article adopts an analysis informed by policy mapping of targeted representative cases combined with a comparative approach towards those cases. It proposes for the subject to be addressed from the perspectives of the states; protection seekers; and the balance of refugees' rights and state security. This article argues that the concept of external burden-sharing is compatible with effective refugee protection and their more rational distribution, but only when it offers long-term solutions based on genuine protection and not as a surrogate to the granting of asylum in the European Union. According to the analysis provided, this article concludes that the current European Union policy on refugee protection is implicitly guided by a restrictive rationalisation of movements as a result of a slow evolution of a distorted and not effectively implemented version of external burden-sharing. First through promoting local solutions and then the human security concept. Yet, this policy cannot represent an acceptable long-term alternative to territorial asylum or an admissible form of external burden-sharing, because protection seekers' movements are guided by the safety and effectiveness of protection and the current European Union external approach does not offer such protection.